IN HOUSE TRAINING SEBAGAI UPAYA PENINGKATAN KOMPETENSI LITERASI IT GURU PADA MASA PANDEMIK DI SDN PURWOSARI 02 KOTA SEMARANG - Kristyanti, Anik (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
The demanding COVID-19 pandemic period requires teachers to always be alert to various conditions regarding online learning. This is certainly a new phenomenon for teachers and makes a new responsibility for the success of student learning outcomes with the demands of mastering IT on the teacher, but not all teachers including teachers at SDN Purwosari 02 Semarang City have IT literacy competence, many teachers are clueless in doing learning process, so that the learning process uses only one learning, namely WA by sending assignments to students and students sending them back to teachers without any other innovations in the use of Web-based technology, of the 15 teachers at SDN Purwosari 02 Semarang City there are only 6 teachers or 40% who really have IT literacy. Such a situation certainly requires the role of the principal to improve the IT literacy of teachers by conducting supervision by means of In House Training (IHT). This study is intended to answer the problem: is there an increase in teacher IT literacy competence during the pandemic after the In House Training was held at SDN Purwosari 02 Semarang City in the 2020/2021 Academic Year?. These problems are discussed through classroom action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results showed that there was an increase in the IT literacy competence of teachers during the pandemic after the In House Training was carried out at SDN Purwosari 02 Semarang City in the 2020/2021 academic year, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle where in the first cycle there were 11 teachers or 69%, and in the second cycle there were 15 teachers or 94%. These results indicate that these results are in line with expectations.